LEGAL POLITICS IN THE AMENDMENT OF REGIONAL HEAD ELECTORAL LAW - Fayreizha Destika Putri; Ani Purwanti (Fakultas Hukum, Universitas Diponegoro, 2018)
Legal politics means that in every legislations are the result of political calculation from actors in legislative-making. The political context regarding the issue such legislation is based upon has a profound effect in the changing course of that legislation. This paper explores the political calculation, thus legal politics, behind the promulgation of Pilkada (regional leader election) law. It is found that there are two fundamental context within the promulgation of Pilkada; civil society and political party. On the former issue, Pilkada law is intended to encourage more public participation in election as to which the system has been revolutionized into a direct type of election. Meanwhile, the political party tends sought a regulation that will ease their voter mobilization. However, the problem emerges when people starts disinterested with the election which has been stained with dirty competition and nepotism. One can argue that if this problem has not been solved in the foreseeable future, the negative impact will be a disarray of social harmony divided by politically-driven social categories.